Growth Pattern and Prevalence of Underweight and Stunting Among Rural Adolescents - Bisai, S; Bose, K; Ghosh, D; De, K (Journal of Nepal Paediatric Society, 2011)
Introduction: A cross-sectional study of 1094 (boys = 665; girls = 429) rural school children aged 11- 18 years of Midnapore Sadar North subdivision, Paschim Medinipur District, West Bengal, India, was undertaken to evaluate their growth pattern and nutritional status. Methodology: Anthropometric measurements including weight and height were measured following standard techniques. Underweight and stunting were used as indicators of nutritional status. Underweight and stunting were defined as weight-for-age (WAZ) and height-for-age (HAZ) <-2 z-scores, respectively, of the National Centre for Health Statistics (NCHS) guidelines. Results: Results revealed that boys were significantly heavier than girls from age 16 onwards; they were also significantly taller from age 14 years. The mean WAZ for boys and girls were -1.488 and -1.417, respectively. The corresponding mean values for HAZ were -1.317 and -1.486. The overall rates of underweight and stunting were 28.3% and 27.8%, respectively. The prevalence of underweight was significantly higher among boys (31.0%) than girls (24.2%). These rates for stunting were 27.4% and 28.4%, for the boys and girls. The rate of underweight and stunting was more in late adolescents (15-18 years) than early adolescents (11-14 years). In boys, the prevalence of stunting was significantly (1.5 times) more in late adolescents than early adolescents. According to the WHO classification for assessing severity of malnutrition, the rates of stunting were medium in both sexes. The rates of underweight were high and very high for girls and boys, respectively. Conclusion: In conclusion, present study provided evidence that the nutritional status of these adolescents were not satisfactory especially among late adolescents. Key Words: Adolescent; Rural; Nutritional Status; Underweight; Stunting DOI: 10.3126/jnps.v31i1.3640 J Nep Paedtr Soc 2010;31(1):17-24